Where is the lifestyle medicine in the Canadian undergraduate medical education curricula? A content analysis (Canadian Medical Education Journal, 2025)
Background: Lifestyle Medicine (LM) focuses on preventing and managing non-communicable diseases (NCDs) through evidence-based behavioural and therapeutic interventions. Despite the established efficacy of LM, its integration into Canadian undergraduate medical education (UGME) remains largely unexamined.Methods: We employed a deductive and inductive summative content analysis methodology. We collected publicly available course and program descriptions for each UGME program across Canada. Further, we contacted deans/curriculum leads for additional curriculum documentation. Documents were coded according to references to various domains of LM as defined by the American College of LM and British Society of LM.Results: The sample comprised 13 UGME programs, with 1327 documents included for the final review. Notable variability across institutions was noted with reference to LM integration. LM topics were more frequently included in pre-clerkship and required courses compared to clerkship and electives. Notably, nutrition, mental wellbeing, and physical activity were most frequently referenced, while sleep health and social connectedness were less represented.Conclusions: To our knowledge, this study is the first to formally map the current practices of LM integration in Canadian UGME. Although there were some study limitations (e.g., exclusion of 25% of Canadian UGME programs), this mapping is integral to identify the current state of the curricula and inform future educational initiatives to enhance medical trainees’ LM-related knowledge and skills. This in turn, may potentially help address modifiable risk factors for NCDs and improve population health outcomes.